Examining a Novel Legacy Activity for Elders: Oral Histories as Produced Stories - Tony H. Liu; Andrea Vernon-Cwik; Sandy Tun (Palliative Medicine Reports, 2024)
Background: Many African American elders who participated in The Great Migration are in the latter years of their lives. One way to maintain their memories and those of elders at large is through legacy activities, projects that initiate a life review process resulting in a product surviving after an individual's death. However, literature on culturally attuned legacy activities as well as measurement of impact are limited. Objectives: This project sought to introduce a novel legacy activity for elders?the oral history as produced aural self-story?detailing its creation and examining its therapeutic efficacy. Design, Setting, and Subjects: Nine African American elders who experienced The Great Migration receiving care from an urban, geriatric clinic were recruited. Oral histories were conducted, produced into aural self-stories, and examined with follow-up interviews and a project evaluation survey. Qualitative analysis of the follow-up interview and a project evaluation survey were used to ascertain therapeutic outcomes. Results: All participants recommended the project and found self-story listening meaningful or beneficial. Qualitative interviews produced 13 codes; the five most frequent were reflection/contemplation (n?=?18), sentimentality/positive affect and affirmation/enlightenment (n?=?10), as well as empathy/gratitude and curiosity/intrigue/peculiarity (n?=?7). Conclusion: Our project suggests that aural self-stories produced from oral histories enhance the current elder legacy activity landscape by facilitating meaning and existential affirmation, additionally leaving a product for subsequent generations. Future studies include comparison to existing legacy interventions and project examination in additional elder populations.